Tecnologias digitais na educação: formação e prática docente - Fogliato, Charline Lunardi (2024)
This study, linked to the Management of Networked Educational Technologies research line, of the Postgraduate Program in Networked Educational Technologies at UFSM – RS, addresses the contributions of training in Digital Information and Communication Technologies (DICTs) in the practice of educators. For this, the training offered through the Compartir extension project of the Instituto Federal Farroupilha (IFFar) was considered, in the period from 2020 to 2022. Therefore, it encompassed four municipal education networks in Rio Grande do Sul (RS), namely: Canguçu, Santa Maria, Santiago and São Vicente do Sul. The search for innovative education requires the incorporation of digital technologies in teaching processes, given their presence in contemporary culture. However, effective use demands appropriate methodologies and infrastructure; and by training educators and students. In the latter case, Higher Education Institutions (HEIs), through extension, can help improve teaching knowledge by offering training that considers the specificities of the context in question and the practices developed by these educators. In order to gain an understanding of the potential of the training offered by the Project, the research had the general objective of analyzing the impact of training on digital technologies, offered by the Compartir project, on the practice of educators. Regarding characterization, the research is of an applied nature, with a qualitative approach, descriptive objectives and in terms of procedure, it is classified as a case study. An online questionnaire was used as a data collection instrument, and the data collected was analyzed using content analysis. The main results showed that knowledge about DICTs is shared among teachers in the school environment, is recognized as knowledge in demand in contemporary times and was enhanced by the Covid-19 pandemic, which also boosted investments in technological infrastructure for schools, and currently the teachers have access, but highlight the poor quality of wireless internet. The results also revealed that DICTs are being used in practice, through the planning and execution of classes, and in activities developed with students, including in contemporary teaching methodologies, due to teachers understanding that TDIC are allies of student learning. With this, it is concluded that the Compartir extension project had an impact on teaching practice as it contributed to learning and aspects that enhance the construction of knowledge, directly and indirectly reflecting on pedagogical practice, the use of infrastructure and the exchange relationship with peers and students. Based on this investigation and the experience with teacher training, the guide “Continued Teacher Training - possibilities in virtual environments” was created, which is the educational product of the dissertation.